Nuclei in a supersaturated solution. Utrecht chemists and the crystallization of international relations after the First World War - Smit, Jorrit (Studium, 2014)
The mobilization and involvement of chemists in the First World War revealed the protean nature of science. This harsh knock to the pre-war optimistic views on the societal role of science reverberated the following decade in the deeply divided international scientific community. In the dark shadows of the war and the breakdown of scientific internationalism, the Utrecht chemists Ernst Cohen and Hugo Kruyt attempted to lighten up the international sphere of chemistry. This study focusses on their main informal effort to reunite chemists from former belligerent nations at the 1922 ‘International Chemical Reunion Utrecht’. This is the first detailed empirical elaboration of the thesis that reconstruction in the 1920s proceeded most importantly through unofficial contact. Despite recent scepticism about this historiographical image in general and the impact and political insight of these Dutch mediators in particular, this article argues that they acted empathically and achieved a unique success in the scientific world. Although science failed to take a moral leading role in European society, the continuous and subtle activity of the Utrecht chemists in the informal and formal networks of chemistry ultimately led to the only complete restoration of an international scientific community before the advent of the Second World War.